2017
DOI: 10.1186/s12943-017-0692-x
|View full text |Cite
|
Sign up to set email alerts
|

The lncRNA CASC15 regulates SOX4 expression in RUNX1-rearranged acute leukemia

Abstract: BackgroundLong non-coding RNAs (lncRNAs) play a variety of cellular roles, including regulation of transcription and translation, leading to alterations in gene expression. Some lncRNAs modulate the expression of chromosomally adjacent genes. Here, we assess the roles of the lncRNA CASC15 in regulation of a chromosomally nearby gene, SOX4, and its function in RUNX1/AML translocated leukemia.Results CASC15 is a conserved lncRNA that was upregulated in pediatric B-acute lymphoblastic leukemia (B-ALL) with t (12;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 61 publications
2
98
0
1
Order By: Relevance
“…High expression of CASC15 led to myeloidpredominant BM development, decreased engraftment, and colony formation. Researchers also found that CASC15 positively regulated YY1-mediated SOX4 promoter [178].…”
Section: Runx1 Mutation-related Lncrnasmentioning
confidence: 98%
“…High expression of CASC15 led to myeloidpredominant BM development, decreased engraftment, and colony formation. Researchers also found that CASC15 positively regulated YY1-mediated SOX4 promoter [178].…”
Section: Runx1 Mutation-related Lncrnasmentioning
confidence: 98%
“…Here we report that a lncRNA, named CASC15, is transcriptionally activated by the hypoxia/HIF-1α signaling and promotes SOX4 expression in a cis-acting manner in NSCLC. CASC15 was firstly identified as a pivotal tumor suppressor in neuroblastoma but was later reported to play an oncogenic role in many other cancer types, such as melanoma, gastric cancer, liver cancer, and acute leukemia [21,22,[27][28][29]. Nevertheless, these studies did not uncover the signaling pathways that might activate the expression of CASC15.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that CASC15 expression is elevated in a variety of human malignancies, such as melanoma, gastric cancer, liver cancer, and acute leukemia [22,[27][28][29]. However, to date, little is known about the mechanisms governing CASC15 upregulation in cancer.…”
Section: Casc15 Is Transcriptionally Activated By the Hypoxia/hif-1α mentioning
confidence: 99%
“…With the continuous improvement and progress of experimental technology, more and more new lncRNAs have been discovered by RNA sequencing technology, which play a main role in the occurrence and development of diseases and malignant progress [2,25,37]. Many studies have shown that many lncRNAs express differently in AML and can regulate their functions [11,12,21,30]. However, the function and molecular mechanism of many lncRNAs associated with AML are still unclear.…”
Section: Discussionmentioning
confidence: 99%